The effectiveness of self-efficacy-based motivational interview on increasing medication adherence in women with type-2 diabetes - Jafarzadeh, Naser; Mirzahoseini, Hassan; Monirpour, Nader (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to determine the effectiveness of self-efficacy-based motivational interview intervention on increasing medication adherence in women with type 2 diabetes. Method: The current study is a quasi-experimental study with a pre-test, post-test, and follow-up design and a available sampling method, which was conducted on 30 type-2 diabetes patients, members of the Tehran Diabetes Research Institute, who were eligible to participate in the study in 2017. The data were collected using the eight-item Morisky Medication Adherence Scale (2008) and the demographic questionnaire by interviewing and taking blood samples. Each member of the intervention group underwent five 30-to-45-minute sessions of motivational self-efficacy-based interviews based on self-efficacy. Data were analyzed using a variance of repeated measures. Results: The findings showed that self-efficacy-based motivational interview significantly reduced medication adherence (F=23.73, Sig=0.000) of patients with type 2 diabetes, and this effect was in the stable follow-up phase. Conclusion: The motivational self-efficacy-based interview intervention in five sessions positively affected medication adherence in type 2 diabetes patients. Therefore, it is suggested that this intervention be done in more time and sessions.